Can high-frequency mini-probe endoscopic ultrasonography predict outcome of endoscopic dilation in patients with benign esophageal strictures? - Daniel, Philip; Samanta, Jayanta; Gulati, Ajay; Gupta, Pankaj; Muktesh, Gaurav; Sinha, Saroj K.; Kochhar, Rakesh (Endoscopy International Open, 2020)
Background and study aims Endoscopic dilation is first-line management for benign esophageal strictures (ES). Depth of involvement of the esophageal wall on endosonography using high frequency mini-probe (EUS-M) may predict response to dilation. This study evaluated EUS-M characteristics to predict response of ES to endoscopic dilation.Patients and methods EUS-M was used to measure the total esophageal wall thickness (EWT), involved EWT, percentage of involved wall and layers of wall involved in consecutive patients of benign ES. After a maximum of five sessions of endoscopic dilation, the cohort was divided into responders and refractory strictures. EUS-M characteristics were compared for underlying etiology as also between responders and refractory strictures.Results Of the 30 strictures (17 females, age: 47.16 ± 15.86 yrs.) 13 were anastomotic, eight corrosive, seven peptic and 2 others. Corrosive strictures had the highest involved EWT and percentage of involved wall (3.51 ± 1.36 mm; 76.38 %) followed by anastomotic (2.73 ± 1.7 mm; 65.54 %) and peptic (1.39 ± 0.62 mm; 40.71 %) (P = 0.026 and 0.021 respectively). After five dilations, 22 were classified as responders and eight as refractory. Wall involvement > 70 % had a greater proportion of refractory strictures (P = 0.019). Strictures with involved EWT of ≥ 2.85 mm required more dilations (P = 0.011). Fewer dilations were required for stricture resolution with only mucosal involvement compared to deeper involvement such as submucosa and muscularis propria (2.14 vs. 5.80; P = 0.001). Conclusion EUS-M evaluation shows that corrosive and anastomotic strictures have greater depth of involvement compared to peptic strictures. Depth of esophageal wall involvement in a stricture predicts response to dilation.